Perspective on big data system computing technology - Haitao WANG; Rui MAO; Zhong MING (大数据)
The state of the art of big data system computing technology was elaborated and the big data system computing innovation platform at the National Engineering Laboratory for Big Data System Computing Technology was introduced.The platform strives to develop China-made general-purpose big data computing system,to conquer common problems in high performance big data computing,and to develop applications.The construction of the platform will boost national big data innovation capability,fulfill the demand of big data technology and application in China,promote the big data industry,and help the construction of big data “double-innovation” eco-system.